Praedial Servitude as a Legal-Dogmatic Model in the Period of the Usus Modernus Pandectarum (Zemljiška služnost kot pravnodogmatični model v obdobju usus modernus pandectarum) - Vid Žepič (Zbornik Znanstvenih Razprav, 2020)
For learned jurists of the 16th–18th centuries, Roman praedial servitudes represented a legal-dogmatic model for conceptualisation and incorporation of heterogeneous feudal institutions into the categories of the ius commune. The author explains the reasons for a peculiarly wide understanding of praedial servitudes and outlines the issues learned ju-rists had to overcome while dealing with the harmonisation of Roman law and particular law tradition. An overview of manifestations of servitudes including the legal relations on the common land, legal servitudes, serfdom, banalités, regalia and international ser-vitudes is concluded with their conceptual analysis. The author demonstrates that the content of praedial servitudes in the the usus modernus period differed substantially from the notion of the ancient Roman Law as well as of the modern civilistic science.